Regional Differentiation of Information Infrastructure in Poland in the Context of Building a Knowledge-Based Economy - Wioletta Wierzbicka (Institute of Economic Research (IER), 2017)
Information infrastructure creates the key infrastructure of the knowledge-based economy. The widespread use of information and communication technologies contributes not only to the increased efficiency of individual economic entities, but also to the possibilities of enhancing the entire economy. Information infrastructure is also a significant determinant in the development of territorial units, and therefore, it influences the regional dimension of building knowledge-based economy in Poland. The purpose of the study was the evaluation of the regional differentiation of the level of information infrastructure in Poland, and changes which occurred in this respect between 2010 and 2015. The following research hypothesis was formulated: Regional differentiation of the level of information infrastructure in Poland is decreasing, i.e. a regional convergence process is taking place in this respect. The study was performed at the regional NUTS II level. Taxonomic methods, including linear ordering based on a synthetic variable and a method of grouping linearly-ordered objects, were used. The regional differentiation of the level of information infrastructure in Poland is at an average level, whereas the scale of this differentiation has slightly decreased. This may be confirmed by the value of the variation coefficient, which fell from the level of 17.6% in 2010 to the level of 14.4% in 2015. The regional convergence with respect to the level of information infrastructure in Poland was accompanied by the internal convergence and divergence of provinces. In consequence of such processes, the position of individual provinces with respect to others, has changed quite significant. Into the group of provinces with a very high ICT level were classified three provinces: Mazowieckie, Dolnoslaskie and Pomorskie. The group of provinces with very low ICT level includes: Lubelskie, Swietokrzyskie and Zachodnipomorskie.
Keywords: O30; O33; R11; 330; information infrastructure; regional differentiation; knowledge-based economy